Effects of NSAIDs on Bladder Function in Normal and Cystitis Rats: a Comparison Study of Aspirin, Indomethacin, and Ketoprofen - Hiroko Takagi-Matsumoto; Betty Ng; Yasuhiro Tsukimi; Masaomi Tajimi (Elsevier, 2004)
To clarify the potential usefulness of non-steroidal anti-inflammatory drugs, NSAIDs, for patients with overactive bladder, we examined the effect of NSAIDs on urodynamic parameters in normal and cystitis rats and compared their ulcerogenic activity in the gastrointestinal mucosa. Cystometry was performed after administration of the conventional NSAIDs, aspirin, indomethacin, or ketoprofen. Prostaglandin levels were measured in the bladder of cystitis rats pretreated with NSAIDs. Furthermore, the ulcerogenic responses were examined. NSAIDs increased bladder capacity without any effect on micturition pressure in normal rats in the following rank order of potency: ketoprofen ≥ indomethacin ≥ aspirin. In cystitis rats, bladder capacity was increased and micturition frequency was decreased. The levels of prostaglandin were significantly increased in cystitis rats. All NSAIDs inhibited the increment of prostaglandin levels at doses equal to that effective in the improvement of bladder functions. When administered intraduodenally, both ketoprofen and indomethacin induced lesions in the gastrointestinal mucosa. However, aspirin had no significant effect. We demonstrate that NSAIDs are effective in animal models of disease, most likely by suppressing by prostaglandin synthesis. Since aspirin, in contrast to ketoprofen or indomethacin, did not cause any gastrointestinal lesions, aspirin might be the NSAIDs treatment of choice for overactive bladder. Keywords:: aspirin, non-steroidal anti-inflammatory drug, overactive bladder, urodynamic parameter, gastrointestinal lesion